Training on Processing Local Products (Naget Fish) in Improving the Nutritional Status of the Community in Mamboro District, Central Sumba Regency - David Loba; Didik Cahyono (PT FORMOSA CENDEKIA GLOBAL, 2022)
Fish is a source of animal protein that is consumed by many people because it is relatively easy to obtain and the price is affordable. Attention to low-priced fish and its process into a more expensive food ingredient is what is needed by countries that have large fishery resources, especially in Indonesia. Fish nuggets are food products derived from ground fish with the addition of spices and printed, which is then smeared with coatings (coating and breading), then frying (Rosselinda et al, 2018). Fish nuggets are an alternative to nuggets that contain good nutrition. These fish nuggets contain protein, fat and vitamins which are beneficial to the body and can be used as a side dish for food. Whereas the BUMDes Business Unit is a business entity owned by the Village BUMDes that carries out activities in the economic sector or public services with a legal entity that carries out the functions and objectives of the Village BUMDes. The science of sports nutrition is the application of nutrition to athletes so that they are able to achieve optimal performance.